2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944050
|View full text |Cite
|
Sign up to set email alerts
|

Smart phone monitoring of second heart sound split

Abstract: Heart Auscultation (listening to heart sounds) is the basic element of cardiac diagnosis. The interpretation of these sounds is a difficult skill to acquire. In this work we have developed an application to detect, monitor, and analyze the split in second heart sound (S2) using a smart phone. The application records the heartbeat using a stethoscope connected to the smart phone. The audio signal is converted into the frequency domain using Fast Fourier Transform to detect the first and second heart sounds (S1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Also in the case of the components of the second heart sound, the experimental values we obtained are compliant with the physiological ranges reported in the literature and to the results obtained in former studies [1,23,24,25]. In particular, the second heart sound is expected to occur approximately 300 ms after the first one [1], which is coherent with the values reported in Table 4.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Also in the case of the components of the second heart sound, the experimental values we obtained are compliant with the physiological ranges reported in the literature and to the results obtained in former studies [1,23,24,25]. In particular, the second heart sound is expected to occur approximately 300 ms after the first one [1], which is coherent with the values reported in Table 4.…”
Section: Resultssupporting
confidence: 91%
“…In terms of heart sound components, few detection algorithms [23,24,25,30] are reported in literature, especially concerning the first heart sound. When considering the approach described in this work, it must be observed that when a heart sound is correctly segmented both its components are identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensor data from an edge computing application is commonly sent longer distances to a server. Smartphones are capable of harnessing built-in sensors, such as the microphone or gyroscope, for medical purposes 39,40 . Unlike wearable and smartphone-based sensors, which are physically closer to the patient, ambient sensors are placed around a room or number of rooms to collect data on user position without the patient wearing them.…”
Section: Figurementioning
confidence: 99%
“…In recent years, many mobile POCT devices have been introduced including POCT devices based on low-cost consumer electronics technologies such as smartphones or tablets, which have sophisticated computing capabilities and are widely available in LMICs [ 5 ]. These devices have been integrated into several types of transducers to provide new capabilities such as smartphone attachments for stethoscopes [ 6 , 7 , 8 ], smartphone-based ambulatory blood pressure monitoring [ 8 , 9 , 10 , 11 , 12 ], mobile point-of-care ultrasound [ 13 ], or digital microscopy [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. New assay technologies such as lateral flow, paper-based microfluidics [ 23 ], phone-based colorimetric readers [ 24 ], or lab-on-a-chip (LOC) were used for the development of sensitive, low-cost biological assays [ 25 ].…”
Section: Introductionmentioning
confidence: 99%